2022
DOI: 10.3389/fped.2022.825841
|View full text |Cite
|
Sign up to set email alerts
|

Impairments in Pulmonary Function in Fontan Patients: Their Causes and Consequences

Abstract: Patients with a Fontan circulation lack a sub-pulmonary ventricle with pulmonary blood flow passively redirected to the lungs. In the Fontan circulation, ventilation has a significant influence on pulmonary blood flow and cardiac output both at rest and with exercise. Children and adults with a Fontan circulation have abnormalities in lung function. In particular, restrictive ventilatory patterns, as measured by spirometry, and impaired gas transfer, as measured by the diffusing capacity of carbon monoxide, ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 101 publications
1
7
0
Order By: Relevance
“…Studies investigating lung function in Fontan patients are limited, but it seems evident that impaired lung function is common [ 10 , 11 , 13 , 14 , 28 ]. In our study, we observed a restrictive lung pattern and a severely reduced DLCO and DLNO in both PFT-I and PFT-II, consistent with previous reports [ 29 ]. To our knowledge, no previous longitudinal studies are available for comparison of the development of lung function over time in Fontan patients.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Studies investigating lung function in Fontan patients are limited, but it seems evident that impaired lung function is common [ 10 , 11 , 13 , 14 , 28 ]. In our study, we observed a restrictive lung pattern and a severely reduced DLCO and DLNO in both PFT-I and PFT-II, consistent with previous reports [ 29 ]. To our knowledge, no previous longitudinal studies are available for comparison of the development of lung function over time in Fontan patients.…”
Section: Discussionsupporting
confidence: 93%
“…The exact pathophysiology behind the impaired lung function in Fontan patients remains unclear, but several concepts are discussed in a 2022 review by Laohachai and Ayers [ 29 ]. The negative impact of a non-pulsatile pulmonary flow on lung function is the most discussed theory.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the Fontan circulation, a preserved inspiratory function is more important than in other patients ( 16 ). In contrast to biventricular circulation, in Fontan patients, inspiration represents the main driving force for atrial and ventricular filling and therefore the most critical component for cardiac output at rest and during exercise, whereas myocardial contraction acts as a pump for forward flow ( 3 , 16 ). A restrictive pattern of lung function is frequently found in Fontan patients ( 13 , 14 ) and has been described to correlate with reduced exercise capacity and quality of life ( 15 , 16 ).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to biventricular circulation, in Fontan patients, inspiration represents the main driving force for atrial and ventricular filling and therefore the most critical component for cardiac output at rest and during exercise, whereas myocardial contraction acts as a pump for forward flow ( 3 , 16 ). A restrictive pattern of lung function is frequently found in Fontan patients ( 13 , 14 ) and has been described to correlate with reduced exercise capacity and quality of life ( 15 , 16 ). In our study, we found a similarly high prevalence of restrictive lung disease, with up to 33% of patients with pathologically diminished FVC.…”
Section: Discussionmentioning
confidence: 99%